Multi‐ancestry genome‐wide association study of asthma exacerbations. Issue 6 (8th June 2022) - Herrera‐Luis, Esther; Ortega, Victor E.; Ampleford, Elizabeth J.; Sio, Yang Yie; Granell, Raquel; de Roos, Emmely; Terzikhan, Natalie; Vergara, Ernesto Elorduy; Hernandez‐Pacheco, Natalia; Perez‐Garcia, Javier; Martin‐Gonzalez, Elena; Lorenzo‐Diaz, Fabian; et al.
Abstract: Background: Asthma exacerbations are a serious public health concern due to high healthcare resource utilization, work/school productivity loss, impact on quality of life, and risk of mortality. The genetic basis of asthma exacerbations has been studied in several populations, but no prior study has performed a multi‐ancestry meta‐analysis of genome‐wide association studies (meta‐GWAS) for this trait. We aimed to identify common genetic loci associated with asthma exacerbations across diverse populations and to assess their functional role in regulating DNA methylation and gene expression. Methods: A meta‐GWAS of asthma exacerbations in 4989 Europeans, 2181 Hispanics/Latinos, 1250 Singaporean Chinese, and 972 African Americans analyzed 9.6 million genetic variants. Suggestively associated variants ( p ≤ 5 × 10 −5 ) were assessed for replication in 36, 477 European and 1078 non‐European asthma patients. Functional effects on DNA methylation were assessed in 595 Hispanic/Latino and African American asthma patients and in publicly available databases. The effect on gene expression was evaluated in silico. Results: One hundred and twenty‐six independent variants were suggestively associated with asthma exacerbations in the discovery phase. Two variants independently replicated: rs12091010 located at vascular cell adhesion molecule‐1/exostosin like glycosyltransferase‐2 ( VCAM1 / EXTL2 ) (discovery: odds ratio (ORT allele ) = 0.82, p = 9.05 × 10 −6 and replication: ORT allele = 0.89, p = 5.35 × 10 −3 ) and rs943126 from pantothenate kinase 1 ( PANK1 ) (discovery: ORC allele = 0.85, p = 3.10 × 10 −5 and replication: ORC allele = 0.89, p = 1.30 × 10 −2 ). Both variants regulate gene expression of genes where they locate and DNA methylation levels of nearby genes in whole blood. Conclusions: This multi‐ancestry study revealed novel suggestive regulatory loci for asthma exacerbations located in genomic regions participating in inflammation and host defense. Abstract :